L’autocorrosione del carattere di una generazione. Cosa ha plasmato nei boomer un’identità programmaticamente incoerente - Giuseppe A. Micheli (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The characterization of boomers (even in their later maturity) has always been dual-sided, highlighting at times their identity awareness and at others the strong external influences shaping their social construction. This article outlines the formation of their character across the life course from an internalist historiographical perspective, one rooted not in external socio-technical contingencies but in a process of self-modification driven by internal dynamics, beginning with a “disturbed imprinting” experienced twice. The first disturbance occurred during their transition to adulthood when, faced with the inheritance of a rights-based and Welfare society generously octroyée by their forebears, perceived as a discouraging finis historiae, boomers reacted through opposition. They complemented the eudaimonic aspirations of the era with a widespread strategy of “exaggeration”. The second disturbance emerged at the turn of the 1970s, as disenchantment surfaced alongside an acceleration of “diversionary strategies”, boomers, driven by crisis-induced mindsets and exposed to the pressure of particularly harmful pragmatic paradoxes, responded with strategies of disconfirmation, manifesting as individual crisis behaviors. Thus, faced with a twice-disturbed imprinting, boomers adapted along the way, arriving at a contradictory social mask. A central feature of this mask is the legitimization of the right to inconsistency, which, in a surprising trajectory, shifted from an ought rule to mere transgression, eventually devolving into a residual norm.